Financial Sanctions for Breach of Shareholders’ Duties - Payne, J; Howell, E (SSRN, 2018)
Shareholders’ duties can arise in a number of ways: by agreement between the shareholders contractually; by agreement via the company’s constitution, and by imposition of law, whether that is by way of legislation or a judicial decision. Effective remedies are needed if these duties are not fulfilled, in order to deter non-compliance, and to provide compensation where relevant. This chapter will discuss the benefits of financial sanctions as a remedy for breach of shareholders’ duties and explore the availability and likelihood of financial sanctions where such duties are breached. Actions by other shareholders for breach of duty (whether via contractual claims or otherwise) will be compared and contrasted with potential actions by regulators. It will be argued that financial sanctions can be a useful weapon in the armoury of those faced with the possibility of a breach of shareholders’ duties.